Quality of Life in Acromegaly Disease Among Iranian Population:One Longitudinal Before-After Study - Arezoo Chouhdari; Farnaz Saberian; Omidvar Rezaei; Mohammad Samadian; Kaveh Ebrahimzadeh; Guive Sharifi; Zahra Davoudi (Shiraz University of Medical Sciences, 2023)
Background: The current study aimed to determine the quality of life (QoL) scores before and after treatment in patients with acromegaly.Methods: In this longitudinal before-after study, the acromegaly quality of life (AcroQoL) questionnaire was used to assess the QoL. Demographics, clinical manifestations and co-morbidity data, pituitary axis involvement, biochemical and hormonal component tests, and health-related quality of life (HRQoL) before and after treatment (endoscopic transsphenoidal surgery, medication, radiotherapy) were evaluated in patients over 18 years of age. To compare the mean of continuous data, the independent t and Mann-Whitney tests were used. To compare the mean QOL score before and after the study, the paired-t and Wilcoxon tests were performed. The significance level was set at p<0.05.Results: Among 80 patients with acromegaly who underwent trans-sphenoid surgery with or without radiotherapy or medication therapy with somatostatin analogs, 52 (65%) entered the remission phase within 6 months. Associations were found between the remission phase and female gender (p=0.004) and lower growth hormone (GH) (p=0.04) but not between remission and lower insulin-like growth factor-I (IGF1) after surgery (p=0.02) or gonadal axis disorder after treatment (p<0.001) statistically. Moreover, a significant association was found between not being in the remission phase and gonadal axis disorder before treatment (p=0.04). The QoL score in all dimensions of the AcroQoL questionnaire increased 6 months after treatment (p<0.001). Total AcroQoL score was higher after treatment in the remission group (p=0.03). The psychological scale had a significantly higher score both on the total scale (p<0.001) and on the two subscales of appearance (p<0.001) and personal relationship (p=0.003).Conclusion: Because of the importance of QoL in acromegaly patients, further studies in this field are recommended.